Molecular shape-selectivity of MFI zeolite nanosheets in n-decane isomerization and hydrocracking - Verheyen, Elke; Jo, Changbum; Kurttepeli, Mert; Vanbutsele, Gina; Gobechiya, Elena; Korányi, Tamás I.; Bals, Sara; Van Tendeloo, Gustaaf; Ryoo, Ryong; Kirschhock, Christine E.A.; Martens, Johan A. (Journal of catalysis, 2013)
n-Decane is shape-selectively converted inside the short straight channels crossing MFI nanosheets even when only one unit cell thick. [Display omitted] ► MFI zeolite nanosheets were transformed into bifunctional catalysts. ► MFI nanosheets with one unit cell thickness behave zeolite like. ► MFI nanosheets display transition-state shape-selectivity similar to bulk zeolite. ► As expected, in MFI nanosheets diffusion-based selectivity is less pronounced. MFI zeolite nanosheets with thickness of 2 and 8nm were synthesized, transformed into bifunctional catalysts by loading with platinum and tested in n-decane isomerization and hydrocracking. Detailed analysis of skeletal isomers and hydrocracked products revealed that the MFI nanosheets display transition-state shape-selectivity similar to bulk MFI zeolite crystals. The suppressed formation of bulky skeletal isomers and C5 cracking products are observed both in the nanosheets and the bulk crystals grown in three dimensions. This is typical for restricted transition-state shape-selectivity, characteristic for the MFI type pores. It is a first clear example of transition-state shape-selectivity inside a zeolitic nanosheet. Owing to the short diffusion path across the sheets, expression of diffusion-based discrimination of reaction products in the MFI nanosheets was limited. The 2-methylnonane formation among monobranched C10 isomers and 2,7-dimethyloctane among dibranched C10 isomers, which in MFI zeolite are favored by product diffusion, was much less favored on the nanosheets compared to the reference bulk ZSM-5 material.